Dark Energy Survey year 1 results: galaxy sample for BAO measurement. Issue 2 (14th September 2018) - Crocce, M; Ross, A J; Sevilla-Noarbe, I; Gaztanaga, E; Elvin-Poole, J; Avila, S; Alarcon, A; Chan, K C; Banik, N; Carretero, J; Sanchez, E; Hartley, W G; et al.
ABSTRACT: We define and characterize a sample of 1.3 million galaxies extracted from the first year of Dark Energy Survey data, optimized to measure baryon acoustic oscillations (BAO) in the presence of significant redshift uncertainties. The sample is dominated by luminous red galaxies located at redshifts z ≳ 0.6. We define the exact selection using colour and magnitude cuts that balance the need of high number densities and small photometric redshift uncertainties, using the corresponding forecasted BAO distance error as a figure-of-merit in the process. The typical photo z uncertainty varies from 2.3 per cent to 3.6 per cent (in units of 1+z ) from z = 0.6 to 1, with number densities from 200 to 130 galaxies per deg 2 in tomographic bins of width Δz = 0.1. Next, we summarize the validation of the photometric redshift estimation. We characterize and mitigate observational systematics including stellar contamination and show that the clustering on large scales is robust in front of those contaminants. We show that the clustering signal in the autocorrelations and cross-correlations is generally consistent with theoretical models, which serve as an additional test of the redshift distributions.